PENGARUH MOTIVASI KERJA DAN STRES KERJA TERHADAP KINERJA PEGAWAI PADA DINAS PEMADAM KEBAKARAN DAN PENYELAMATAN KABUPATEN OGAN KOMERING ULU - Okta Restiana Putri; Rosmala Dewi (Fakultas Ekonomi dan Bisnis Universitas Baturaja, 2020)
This study discusses the Influence of Work Motivation and Job Stress onEmployees’ Performance at the Fire and Rescue Service of Ogan Komering Ulu District.The population in this study was 23 employees. The analytical method used is aquantitative analysis method using multiple linear regression analysis tools. The resultsof the analysis show that partially calculate the Work Motivation variable (X1) (9,507)>t-table (1,724) then Ho is rejected and Ha is accepted, this means that the WorkMotivation variable (X1) significantly influences Employees’ Performance at the Fireand Rescue Service of Ogan Komering Ulu District, calculate the variable Job Stress(X2) (19,558)> t-table (1,724) then Ho is rejected and Ha is accepted, meaning WorkStress (X2) significantly influences the Performance of Employees at the Fire Department Fire and Rescue of Ogan Komering Ulu District. Simultaneously F-count (3394,603)> F-table (3,10), then Ho is rejected and Ha is accepted, this means that the variable Work Motivation and Job Stress together have a significant influence on the Performance ofEmployees at the Fire and rescue Service of Ogan Komering Ulu District. The results ofthe analysis of the coefficient of determination (R Square) is 0.997. This means that thecontribution of the influence of Work Motivation variable (X1) and Job Stress Variable(X2) on Employees’ Performance variables (Y) is 99.7% while the remaining 0.3% isinfluenced by other variables not included in this model such as, responsibility , workdiscipline and incentives. (Prawirosentono, 2012: 28)